2016
DOI: 10.1007/s00482-015-0092-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, tolerability, and safety of cannabinoids for chemotherapy-induced nausea and vomiting—a systematic review of systematic reviews

Abstract: With safe and effective antiemetics available, CBs cannot be recommended as first- or second-line therapy for CINV. Some guidelines recommend pharmaceutical CBs as third-line treatment in the management of breakthrough nausea and vomiting. Due to the lack of RCT data and safety concerns, herbal cannabis cannot be recommended for CINV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 27 publications
0
36
0
1
Order By: Relevance
“…In a case–control study conducted on 163 young men with testicular cancer and 292 control men, the men who had smoked cannabis presented twice as much risk of developing a form of testicular cancer with a poor prognosis compared to those who had not smoked any . Several studies reinforce this view . Nevertheless, in 2017, a Swedish epidemiologic study included near 50 000 men from 1970 to 2011 found no relationships between lifetime ‘ever’ cannabis use and the development of testicular cancer and only heavy cannabis users were associated with a higher incidence of testicular cancer .…”
Section: Social Usage Of Cannabis In Cancermentioning
confidence: 99%
“…In a case–control study conducted on 163 young men with testicular cancer and 292 control men, the men who had smoked cannabis presented twice as much risk of developing a form of testicular cancer with a poor prognosis compared to those who had not smoked any . Several studies reinforce this view . Nevertheless, in 2017, a Swedish epidemiologic study included near 50 000 men from 1970 to 2011 found no relationships between lifetime ‘ever’ cannabis use and the development of testicular cancer and only heavy cannabis users were associated with a higher incidence of testicular cancer .…”
Section: Social Usage Of Cannabis In Cancermentioning
confidence: 99%
“…Only very few cannabis-based drugs, manufactured under stricter standards, are currently marketed under regulatory approval. [25][26][27][28][29] The oral administration of cannabinoids has several advantages: it is easier to consume, dose and composition are more tightly controlled, exposure time is longer, and side effects are considerably less intense. [17][18][19] The bioavailability of cannabinoids varies significantly by their mode of administration.…”
mentioning
confidence: 99%
“…The flowchart of the process of selection of the studies is presented in Figure 1. The list of excluded studies and the reasons for exclusions are stated in Table 2 (Barnes, 2002;Kinzbrunner, 2002;Tafelski, Häuser, & Schäfer, 2016;Verneda, 2002).…”
Section: Search Resultsmentioning
confidence: 99%
“…Nevertheless, other studies show some disparity. Smith et al (2015) concluded that prochlorperazine was similar to cannabinoids, as Machado Rocha concluded that prochlorperazine, alizapride, and Barnes (2002) Wrong study design Kinzbrunner (2002) Wrong study design Tafelski et al (2016) Wrong study design Verneda (2002) Wrong study design AMSTAR (a measurement tool to assess systematic reviews) items are as follows: 1 = a priori design; 2 = duplicate study selection and data extraction; 3 = comprehensive literature search; 4 = inclusive publication status; 5 = list of included/excluded studies provided; 6 = characteristics of included studies provided; 7 = quality assessment of studies; 8 = study quality used appropriately in formulating conclusions; 9 = appropriate methods used to combine studies; 10 = publication bias assessed; and 11 = conflict of interest stated. Scale for item score: 1 = Yes, 0 = No, Can't answer, or Not applicable.…”
Section: Cannabinoids Versus Other Antiemeticsmentioning
confidence: 99%